Numerical simulation of early-age shrinkage effects on RC member deflections and cracking development - P. Bernardi; R. Cerioni; E. Michelini; A. Sirico (Fracture and Structural Integrity)
Shrinkage effects on short-term behavior of reinforced concrete elements are often neglected both in design code provisions and in numerical simulations. However, it is known that their influence on serviceability performance can be significant, especially in case of lightly-reinforced beams. As a matter of fact, the restraint provided by the reinforcement on concrete determines a reduction of the cracking load of the structural element, as well as an increase of its deflection. This paper deals with the modeling of early-age shrinkage effects in the field of smeared crack approaches. To this aim, an existing non-linear constitutive relation for cracked reinforced concrete elements is extended herein to include early-age concrete shrinkage. Careful verifications of the model are carried out by comparing numerical results with significant experimental data reported in technical literature, providing a good agreement both in terms of global and local behavior.